Energy Savings due to passive strategies in contemporary high-rise residential building hot and dry climate - Shreyash Jadhav (International Journal of Environmental Planning and Development Architecture, 2023)
Globally, the development of sustainable design techniques is becoming imperative, particularly with the idea of high-rise structures to keep up with the rapidly expanding cities. Approaching design sustainably by developing various sustainable methods is becoming necessary worldwide. Strategies for passive design may be useful in achieving the social, economic, and environmental goals of sustainability. This paper discusses the importance of passive design strategies in high-rise buildings, particularly in the context of hot and dry climates, to reduce the energy consumption and environmental impact of buildings. The paper presents a literature review of studies that demonstrate the effectiveness of passive design strategies in high-rise apartments and mixed-use buildings. The first study examines an integrated passive design approach to improve the thermal performance of the building envelope for high-rise apartments in Hong Kong. The second study proposes a new approach to passive design strategies based on the traditional courtyard architecture in arid climates and investigates the potential of sky courts in high-rise buildings to reduce energy consumption. This paper aims to highlight the need for advanced green building simulation software to test various passive design strategies in high-rise residential buildings of hot and dry climates to achieve sustainability.
Keywords: High-rise residential buildings; Sustainability; contemporary passive design; hot and dry climate; passive design